2017
DOI: 10.1093/jnci/djx133
|View full text |Cite
|
Sign up to set email alerts
|

Relapse-Free Survival as a Surrogate for Overall Survival in the Evaluation of Stage II–III Melanoma Adjuvant Therapy

Abstract: In high-risk stage II-III melanoma, RFS appeared to be a valid surrogate end point for OS for adjuvant randomized studies assessing interferon or a checkpoint inhibitor. In future similar adjuvant studies, a hazard ratio for RFS of 0.77 or less would predict a treatment impact on OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 52 publications
1
49
0
1
Order By: Relevance
“…The use of RFS to extrapolate long-term survival within the model aligns with recent evidence on the natural history of resected highrisk melanoma. In a meta-analysis of randomized controlled trials of adjuvant interferon, Suciu et al 75 found a high degree of correspondence between the HR for recurrence or death and the HR for death, and concluded that RFS appears to be a valid surrogate endpoint for OS. Five-year data from the EORTC 18071 trial similarly showed that relative reductions in recurrence or death with ipilimumab vs placebo (HR ¼ 0.76) closely aligned with relative reductions in death (HR ¼ 0.72) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of RFS to extrapolate long-term survival within the model aligns with recent evidence on the natural history of resected highrisk melanoma. In a meta-analysis of randomized controlled trials of adjuvant interferon, Suciu et al 75 found a high degree of correspondence between the HR for recurrence or death and the HR for death, and concluded that RFS appears to be a valid surrogate endpoint for OS. Five-year data from the EORTC 18071 trial similarly showed that relative reductions in recurrence or death with ipilimumab vs placebo (HR ¼ 0.76) closely aligned with relative reductions in death (HR ¼ 0.72) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In the adjuvant setting, RFS is a surrogate for OS for both adjuvant interferon and adjuvant ipilimumab. 8 Extrapolating from this, it is assumed that RFS is a surrogate for OS with adjuvant PD-1 inhibitor therapy; therefore, it is expected that -provided the HR is large -RFS is a surrogate for OS with adjuvant PD-1 inhibitor therapy. Based on this, it is expected that studies that have shown a significant improvement in RFS will translate into improvements in OS.…”
Section: Oncologymentioning
confidence: 99%
“…The CGP method was used to adjust the final curve to apply to the model population that was consistent with the approved indication. The OS for nivolumab was estimated using a surrogacy relationship between the RFS HR and OS HR derived from previous adjuvant melanoma studies including two recent trials [15,[26][27][28]. We assumed the proportional hazards assumption is appropriate between nivolumab and observation because this was a reasonable assumption between nivolumab and ipilimumab for RFS and between ipilimumab and placebo for RFS and OS in CA184-029.…”
Section: Partitioned Survival Model: Surrogacy Modelmentioning
confidence: 99%